ANALISIS HEMAT ENERGI PADA SELUBUNG BANGUNAN BIRO LAYANAN PENGADAAN BARANG DAN JASA DINAS PUPR PROVINSI PAPUA DENGAN OTTV - Indah Sari Zulfiana; Bernard Harianja; Muhammad Amir Salipu; Mercyana t. Zebua (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Building performance is a necessity in the context of a sustainable built environment. The design of buildings that involve the study of building performance has been contained in Law Number 30 of 2007 concerning Energy and Government Regulation Number 70 of 2009 concerning Energy Conservation. The purpose of this energy-efficient building analysis is to determine the level of energy savings of the Papua Province Procurement Services Bureau building that uses a shading device as a control for excess solar radiation intensity by using the Overall Thermal Transmitte Value (OTTV) calculation using the energy saving rate parameter based on SNI 6389:2011, where the building is said to be energy efficient if the OTTV shows a figure of less than 45 W/m2. The results show the number 34.02 W/m2, which means the building can be said to be an energy-efficient building.